UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL 96% DAUN KALANGKALA (Litsea angulata Bl) TERHADAP BAKTERI Cutibacterium acnes - Trialiani, Lydia; Saputri, Revita; Sari, Putri Kartika (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Acne is an infectious disease of the face skin caused by the Cutibacterium acnes, which can be treated by utilizing plants. Kalangkala plant (Litsea angulate Bl) is a plant that has antibacterial activity. The purpose of this study is to identify the secondary metabolite compounds in the 96% ethanol extract of Kalangkala leaves (Litsea angulata Bl) and to determine the area of inhibition showing no bacterial growth, as well as the MIC value against Cutibacterium acnes bacteria using the diffusion method.. The research method used in this study is a posttest-only control group design and an experimental research type. Extraction using the maceration method with 96% ethanol solvent. Testing antibacterial activity of the extract using the well diffusion method against C. acnes bacteria with concentrations of 12,5%, 25%, 50%, 75%, 100%, clindamycin 2 µg/disk (positive control), and Na-CMC 0,5% (negative control). Phytochemical screening results ethanol extract 96% Kalangkala leaves (Litsea angulata Bl) contains alkaloid, flavonoid, tannin, saponin, triterpenoid, and phenol. The result of antibacterial activity of 96% ethanol extract of Kalangkala leaves (Litsea angulata Bl) obtained the average diameter result of inhibition zone of 12,5% concentration is 0,00 mm which there is no inhibition zone and at concentrations of 25%, 50%, 75%, and 100%, has 0.46 mm, 1.32 mm, 2.20 mm, and 3.80 mm with a weak category and positive control with an inhibition zone of 20.50 mm has a strong category. Based on the research, it can be concluded that 96% ethanol extract of Kalangkala leaves (Litsea angulata Bl) has antibacterial activity in inhibiting Cutibacterium acnes with a weak category.